Islamic Radio Broadcasting Management (A Study of An-Nashihah 88.2 FM Makassar) - Kusnandar Putra; Kamaluddin Tajibu; Anshar Akil (Jurnal Mercusuar, 2023)
This research is located at Radio An Nashihah 88.2 FM, which is situated at Jalan Baji Rupa No. 6 Makassar, South Sulawesi. The title of the research is "Broadcast Management of Islamic Radio (A Study of Radio An-Nashihah 88.2 FM Makassar)." Based on this title, two research objectives are formulated: firstly, to understand the broadcast management at Radio An Nashihah 88.2 FM Makassar; secondly, to identify the programs on Radio An Nashihah 88.2 FM Makassar that received KPID Awards from 2019 to 2022.This research is of the qualitative field study type, used to describe, elaborate, and reveal a problem. The approach employed in this research is management approach and descriptive content analysis within the field of communication. Data collection techniques include observation, interviews, and documentation. Informants for this study include the main manager of Radio An-Nashihah, program coordinators, event organizers, technical coordinators, and the institutional coordinator of KPID Sulsel. Data analysis is conducted using the Creswell Model, involving raw data processing, organizing, interpreting, coding, describing, connecting, and interpreting data.Based on the research findings, it is observed that Radio An-Nashihah won the Best Religious Program category with the program "Konsultasi Agama" (Religious Consultation). In 2020, it won the Best Inspiring Program category with the program "Sakinah Indonesiaku" (My Peaceful Indonesia). In 2021, it won the Best Public Service Advertisement category with a program related to COVID-19 education. In 2022, Radio An-Nashihah won the Best Entertainment category with the program "Belajar Mengaji Surah Al-Baqarah" (Learning to Recite Surah Al-Baqarah). Based on content analysis, the three program types received percentages as follows: moral programs (akhlak) at 50%, worship (ibadah) at 33.3%, and belief (aqidah) at 16.6%. According to the data, the moral program category received the highest percentage at 50%.The implications of this research are: 1) The broadcast management at Radio An-Nashihah adheres to religious principles. They apply a comprehensive approach in each stage of their activities, starting from meticulous planning, appropriate organization, effective direction, and regular evaluation to ensure well-coordinated elements. 2) Radio An-Nashihah's success in winning awards in various KPID Award categories demonstrates their dedication in delivering messages of Islamic preaching, especially in improving morals, worship, and belief.